Dominant andreev reflection through nonlinear radio-frequency transport - Tingyu Zhang; Hiroyuki Tajima; Yuta Sekino; Shun Uchino; Haozhao Liang (Communications Physics, 2023)
Abstract It is found that Andreev reflection provides a deterministic teleportation process at an ideal normal-superconductor interface, making it behave like an information mirror. However, it is challenging to control the Andreev reflection in a spatially-separated junction due to the mode mixing at the interface. We theoretically propose the laser-induced Andreev reflection between two-component Fermi superfluid and normal states without mode mixing via spatially-uniform Rabi couplings. By analyzing the tunneling current up to the fourth order, we find that the Andreev current exhibits unconventional non-Ohmic transport at zero temperature. The Andreev current gives the only contribution in the synthetic junction system at zero detunings regardless of the ratio of the chemical potential bias to the superfluid gap, which is in sharp contrast to that in conventional junctions. Our result may give a potential impact on theoretical and experimental study of quantum many-body phenomena, and also pave a way for understanding the black hole information paradox through the Andreev reflection as a quantum-information mirror.